Impact of Knowledge, Attitude and Practice on the Management of Type 2 Diabetes Mellitus in Developing Countries: A Review - Gautam, Sanjeev K.; Gupta, Vivek (Current Diabetes Reviews, 2022)
Background: Diabetes is a major metabolic aggressive disease that has exponentially increased around the globe, including both developed and developing countries. The significant change in the lifestyle of people, attributed to the fast-paced living style and dietary conditions, are a few of the core reasons behind the disease. Multiple studies conducted in various developing countries conclude that patient education, along with adhered practices and attitudinal outlook, can significantly help in deterring the ill effects of diabetes mellitus. Objective: The review aimed at understanding the impact of KAP on the management of diabetes mellitus in emerging economies. Methods: Multi-central analytical cross-sectional and prospective studies were conducted for research in multiple countries with median per capita income of 4,000 (developing countries - Ethiopia, Bangladesh, Iraq, Iran, Nigeria, etc.), wherein significant difference was witnessed in the outlook of patients and related stakeholders, who had a decent score of KAP relative to ones with lower scores, towards type 2 diabetes mellitus. Results: Among all the three variables that are capable of managing diabetes - knowledge, attitude and practice (KAP) - knowledge attained a high degree of importance as it served as the initial step to control DM. In developing countries, the ratio of people with knowledge - relating to disease - is significantly dependent on age, socio-economic status and education. As per the previous studies and their corresponding results, educational awareness is of utmost importance in order to eradicate myths and wrong information around the same. Conclusion: The review concludes the importance of patient counseling to modify their KAP towards the disease will be highly effective in countries like India, where the count of diabetes mellitus patients is increasing aggressively. Investment in patient counselling to improve their KAP score will significantly help in palliating the effect of this disease.
Keywords: morbidity